2016
DOI: 10.1248/bpb.b16-00479
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Drug-Metabolizing Enzyme CYP during Mouse Liver Development

Abstract: The drug-metabolizing enzyme CYP is mainly involved in the metabolism of various substances in the liver, such as drugs, endogenous substances, and carcinogens. Recent reports have also revealed that CYP1B1 plays a major role in the developmental process. Because the level of CYP expression is markedly high in the liver, we hypothesize that CYP plays a role in the developmental process of the liver. To verify this hypothesis, we analyzed the expression patterns of various CYP molecular species and their functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…7) In this study, we investigated whether the transient, high expression of CYP26A1 and CYP2R1 also occurred during differentiation from undifferentiated cells to hepatoblasts, using another differentiation system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7) In this study, we investigated whether the transient, high expression of CYP26A1 and CYP2R1 also occurred during differentiation from undifferentiated cells to hepatoblasts, using another differentiation system.…”
Section: Discussionmentioning
confidence: 99%
“…4,6) We previously demonstrated that in both the induction of differentiation of embryonic stem (ES) cells into hepatocytes experiments and the fetal mice experiments, the expressions of CYP2R1 and CYP26A1 were induced prior to the expression of DLK1, a hepatoblast marker. 7) We suggested that CYP2R1 and CYP26A1 may play a role in hepatoblast cell differentiation during the development of the liver.…”
Section: )mentioning
confidence: 93%
See 1 more Smart Citation
“…The CBD levels of the fetal brain were similar to those of other organs. We also report that the CYP3A family involved in CBD metabolism is rarely expressed in the fetal liver during this period (Ochiai et al, 2016;Kitaoka et al, 2018a;Kitaoka et al, 2018b). Therefore, we felt the need to measure CBD levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning metabolism, CBD is oxidized in the adult liver by cytochrome P450 (CYP) 3A at the 6β, 2′, and 4′ positions (Jiang et al, 2011;Ujvary and Hanus, 2016). However, the metabolic activity of CYP3A is significantly lower in the fetal liver than in the adult liver (Ochiai et al, 2016;Kitaoka et al, 2018a;Kitaoka et al, 2018b). Therefore, it is considered that CBD is distributed throughout the entire fetal body with little metabolism in the liver.…”
Section: Introductionmentioning
confidence: 99%